Concept Mapping - An Instructional Strategy - Menon, P. N.; Dutt, Sunil (Journal of Engineering Education Transformations, 1996)
Concept Mapping unlike conventional method is an instructional strategy that can help the students learn meaningfully whatever is taught to them without taking refuge to rate learning. In this paper, the nature of concept mapping, and how this strategy can be meaningfully employed at all levels of education have been dealt with. The paper also gives some guidelines to teachers regarding the activities they should take while teaching through concept mapping in the classroom. Apart from being an instructional strategy, it has got certain educational implications which have been briefly dealt with in this paper. This novel strategy can be further developed for instruction by conducting further researches. Therefore, a brief survey has been made regarding what research activities have already been done in this area, and, the scope of future research.